The role of immune checkpoints in antitumor response: a potential antitumor immunotherapy - Mejía-Guarnizo, Lidy Vannessa; Monroy-Camacho, Paula Stefany; Turizo-Smith, Andrés David; Rodríguez-García, Josefa Antonia (Frontiers in Immunology, 2023)
Immunotherapy aims to stimulate the immune system to inhibit tumor growth or prevent metastases. Tumor cells primarily employ altered expression of human leukocyte antigen (HLA) as a mechanism to avoid immune recognition and antitumor immune response. The antitumor immune response is primarily mediated by CD8+ cytotoxic T cells (CTLs) and natural killer (NK) cells, which plays a key role in the overall anti-tumor immune response. It is crucial to comprehend the molecular events occurring during the activation and subsequent regulation of these cell populations. The interaction between antigenic peptides presented on HLA-I molecules and the T-cell receptor (TCR) constitutes the initial signal required for T cell activation. Once activated, in physiologic circumstances, immune checkpoint expression by T cells suppress T cell effector functions when the antigen is removed, to ensures the maintenance of self-tolerance, immune homeostasis, and prevention of autoimmunity. However, in cancer, the overexpression of these molecules represents a common method through which tumor cells evade immune surveillance. Numerous therapeutic antibodies have been developed to inhibit immune checkpoints, demonstrating antitumor activity with fewer side effects compared to traditional chemotherapy. Nevertheless, it's worth noting that many immune checkpoint expressions occur after T cell activation and consequently, altered HLA expression on tumor cells could diminish the clinical efficacy of these antibodies. This review provides an in-depth exploration of immune checkpoint molecules, their corresponding blocking antibodies, and their clinical applications.